2007
DOI: 10.1051/0004-6361:20077932
|View full text |Cite
|
Sign up to set email alerts
|

The onset of photoionization in Sakurai's Object (V4334 Sagittarii)

Abstract: We investigate the reheating of the very late thermal pulse (VLTP) object V4334 Sgr (Sakurai's Object) using radio observations from the Very Large Array, and optical spectra obtained with the Very Large Telescope. We find a sudden rise of the radio flux at 5 and 8 GHz -from ≤90 µJy and 80 ± 30 µJy in February 2005 to 320 µJy and 280 µJy in June 2006. Optical line emission is also evolving, but the emission lines are fading. The optical line emission and early radio flux are attributed to a fast shock (and not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
30
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 25 publications
8
30
1
Order By: Relevance
“…There is precedent for this fading and this interpretation for Sakuraiʼs Object (V4334 Sgr, a very-late-thermal-pulse born-again star). Its emission line fluxes have also been seen to decline fairly rapidly (with a half-life just under two years) from 2001 to 2006, with the fading attributed to cooling and recombination in the shell after the heating and ionization ended (Van Hoof et al 2007).…”
Section: The Fading Nebulamentioning
confidence: 99%
See 2 more Smart Citations
“…There is precedent for this fading and this interpretation for Sakuraiʼs Object (V4334 Sgr, a very-late-thermal-pulse born-again star). Its emission line fluxes have also been seen to decline fairly rapidly (with a half-life just under two years) from 2001 to 2006, with the fading attributed to cooling and recombination in the shell after the heating and ionization ended (Van Hoof et al 2007).…”
Section: The Fading Nebulamentioning
confidence: 99%
“…Gesicki et al (2014) has found similar problems in accounting for the white dwarf mass distribution, and they have had to postulate an acceleration by a factor of 3 in the evolutionary timescales of Blocker (1995). In his major review on post-AGB stars, Van Winckel (2003) says "the detailed description of the badly known external post-AGB mass loss on top of the mass loss from the nucleosynthetic consumption is crucial for the transition time estimates" for the star crossing the HR diagram in various phases. It might yet be possible for some new model calculation to match the Stingrayʼs evolution, but until then, the LTP idea has a fundamental problem.…”
Section: Fundamental Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial conditions were calculated by CLOUDY. For the evolution of the "born-again" star in the Hertzsprung-Russell-Diagramm the tracks as used in van Hoof et al (2007) were applied.The nebulae of the "born-again" central stars recombine extremely slowly. The hydrogen and helium timescales dominate the whole process.…”
mentioning
confidence: 99%
“…The initial conditions were calculated by CLOUDY. For the evolution of the "born-again" star in the Hertzsprung-Russell-Diagramm the tracks as used in van Hoof et al (2007) were applied.…”
mentioning
confidence: 99%